Clinical Translation of Tissue Engineered Trachea Grafts. (November 2016) - Chiang, Tendy; Pepper, Victoria; Best, Cameron; Onwuka, Ekene; Breuer, Christopher K
Objective: To provide a state-of-the-art review discussing recent achievements in tissue engineered tracheal reconstruction. Data Sources and Review Methods: A structured PubMed search of the current literature up to and including October 2015. Representative articles that discuss the translation of tissue engineered tracheal grafts (TETG) were reviewed. Conclusions: The integration of a biologically compatible support with autologous cells has resulted in successful regeneration of respiratory epithelium, cartilage, and vascularization with graft patency, although the optimal construct composition has yet to be defined. Segmental TETG constructs are more commonly complicated by stenosis and delayed epithelialization when compared to patch tracheoplasty. Implications for Practice: The recent history of human TETG recipients represents revolutionary proof of principle studies in regenerative medicine. Application of TETG remains limited to a compassionate use basis; however, defining the mechanisms of cartilage formation, epithelialization, and refinement of in vivo regeneration will advance the translation of TETG from the bench to the bedside.